Temporalities of the Port, Waterfront and Port City - Hein, Carola (AESOP, 2016)
Ports are the pulse of port cities.1 Looking outward, ports and port cities together give rhythm to the constant daily flows of goods and people around the globe. With repetition, these flows and times write themselves into the urban environment. But within these flows, economic time and citizen time compete. First, in the daily and seasonal rhythm of the port, humans and of machines work at different speeds while also interacting; and that relationship changed dramatically in the 20th century. During the many the centuries that ports and cities were integrated, shipping depended both on the availability of manpower and good climatic conditions. With the increased use of technology since the 19th century, and especially since the containerization that started in 1960s, ports and cities started to move apart, machines took over more jobs, and weather mattered less. Even though ports and cities are no longer spatially intertwined, ports now reach into their neighboring cities and hinterlands, competing daily and seasonally for space and infrastructure and interfering with the slower rhythms of cities, where human time still plays a role.
City on water : 6th AESOP European Urban Summer School 2015, Bremen